The Effect of Adding Watermelon Rind on the Physical and Sensory Characteristics of Durian Ice Cream - Pravitri, Kartika Gemma; Komalasari, Husnita; Nalurita, Indah; Naufali, Muhammad Nizhar (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2024)
This study aims to determine the effect of adding watermelon rind waste on the physical quality of durian ice cream. The design used was a one-factor Randomized Block Design (RBD) with four treatments and three repetitions. The treatments involved different ratios of watermelon rind pulp: 0%, 10%, 20%, and 30%. The observation data were analyzed using a 5% level Analysis of Variance (ANOVA) with Co-Stat software. If there were significant differences, further tests were conducted using the Honest Significant Difference (HSD) test. The research results indicate that watermelon rind pulp in durian ice cream yielded significantly different results regarding overrun percentage, resistance, and sensory parameters including aroma, taste, and texture. The best results for ice cream with added watermelon rind were obtained from the 30% treatment, with a physical characteristic of 73.42% overrun and 20.14 minutes resistance. Durian ice cream with 30% added watermelon rind has sensory characteristics of a slightly watermelon albedo aroma, a somewhat soft texture, and a slightly astringent taste. Therefore, it can be concluded that the addition of watermelon rind waste affects the physical and sensory characteristics of ice cream.